Identification of Risk Factors for Vascular Thrombosis May Reduce Early Renal Graft Loss: A Review of Recent Literature - Anna Krarup Keller; Troels Munch Jorgensen; Bente Jespersen (Journal of Transplantation)
Renal graft survival has improved over the past years, mainly owing to better immunosuppression. Vascular thrombosis, though rare, therefore accounts for up to one third of early graft loss. We assess current literature on transplantation, identify thrombosis risk factors, and discuss means of avoiding thrombotic events and saving thrombosed grafts. The incidence of arterial thrombosis was reported to 0.2–7.5% and venous thrombosis 0.1–8.2%, with the highest incidence among children and infants, and the lowest in living donor reports. The most significant risk factors for developing thrombosis were donor-age below 6 or above 60 years, or recipient-age below 5-6 years, per- or postoperative hemodynamic instability, peritoneal dialysis, diabetic nephropathy, a history of thrombosis, deceased donor, or >24 hours cold ischemia. Multiple arteries were not a risk factor, and a right kidney graft was most often reported not to be. Given the thrombosed kidney graft is diagnosed in time, salvage is possible by urgent reoperation and thrombectomy. Despite meticulous attentions to reduce thrombotic risk factors, thrombosis cannot be entirely prevented and means to an early detection of this complication is desirable in order to save the kidneys through prompt reoperation. Microdialysis may be a new tool for this.